Expression pattern of key microRNAs in patients with newly diagnosed chronic myeloid leukemia in chronic phase. (2nd April 2015) - Fallah, P.; Amirizadeh, N.; Poopak, B.; Toogeh, G.; Arefian, E.; Kohram, F.; Hosseini Rad, S. M. A.; Kohram, M.; Teimori Naghadeh, H.; Soleimani, M.
Summary Introduction Chronic myeloid leukemia (CML) is caused by reciprocal translocation in hematopoietic stem cells (HSCs). This translocation forms the BCR‐ABL1 oncogene, which alters several signaling pathways that control malignancy. CML has three phases: chronic, accelerated, and blast crisis. The microRNAs (miRNAs or miRs) are noncoding RNAs that downregulate their target gene by targeting 3′ UTR of mRNA or through translational inhibition. It has been shown that miRNAs regulate many biological processes, and dysregulation of these regulatory RNAs is involved in disease development, particularly in cancer. The important role of miRNAs as therapeutic agents and biomarkers has been demonstrated in CML patients at different phases of the disease. Methods Stem‐loop reverse transcription polymerase chain reaction was used to characterize differentially expressed miRNAs of leukocytes in the peripheral blood of 50 newly diagnosed CML patients in chronic phase. Results Some onco‐miRNAs were found to be downregulated (miR‐155 and miR‐106), and some tumor suppressor miRs (miR‐16‐1, miR‐15a, miR‐101, miR‐568) were upregulated. Conclusion These results show that very few miRNAs alone would be good candidates for CML diagnosis independently of conflicting results, but together could be an additional tool for CML diagnosis. Moreover, miRNAs might be good candidates for prognosis prediction and CML therapy.